Pengaruh Disiplin Kerja, Dan Motivasi Kerja Terhadap Kualitas Pelayanan Pajak Kendaraan Bermotor Disamsat Karawang - Enzelia Umu Rahmawati; Sungkono (CV. ITTC INDONESIA, 2024)
This research aims to analyze the influence of work discipline and work motivation on the quality of motor vehicle tax services at Samsat Karawang. Samsat Karawang is an institution that has an important role in the administration and collection of motor vehicle taxes, but often faces challenges in maintaining the quality of its services. This research uses quantitative methods by collecting data through questionnaires distributed to motor vehicle owners who pay taxes at Samsat Karawang. The results of the analysis show that both work discipline and work motivation have a significant positive influence on service quality. High work discipline, which includes compliance with rules, consistency and professionalism, has an impact on increasing service efficiency and effectiveness. Work motivation, both intrinsic and extrinsic, increases officers' involvement in their work, which in turn increases public satisfaction with the services provided. Therefore, to improve service quality, it is important for Karawang Samsat to focus on increasing officer discipline and work motivation through training, reward systems, and improving administrative processes. By implementing these strategies, it is hoped that the quality of service at Karawang Samsat can be better, increase public satisfaction and loyalty, and strengthen the image of public services at the local level.